Neuroaesthetics and landscape appreciation. (2nd January 2021) - Jacques, David
ABSTRACT: This article is a critical review of some aspects of theories of landscape appreciation in the light of the findings of neuroscience. Four propositions that have been employed in appraisal theory, and which can potentially be informed by these findings, are selected. An introduction is given on the scope of neuroscience and its models of aesthetic experience followed by reviews of objectivism, preferences from adaptation, the objective assessor, and direct perception. The conclusions of neuroaestheticians, even in their preliminary present state, offer the potential for clarifying these, and perhaps further, aspects of the theory of landscape assessment.